MENINGKATKAN KEMAMPUAN SISWA DALAM MEMBACA PUISI DENGAN METODE DEMONTRASI DI KELAS V SD NEGERI 005 KOTO PERAMBAHAN KECAMATAN KAMPAR KABUPATEN KAMPAR - Rahmani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This research aims to increase students ability in reading poetry with demonstration methods in class V SD Negeri 005 Koto Perambahan Kecamatan Kampar Kabupaten Kampar. The subject of this research is the students class V with the number of students 28. The research was conducted two cycles. Each cycle is done several stages is action planning, action implementation, observation and evaluation, and reflection. The results of research showed that in cycle I total of complete students is 8 students or 28.6% with low category. In the cycle II the number of completed students increased to 25 students or 89.2% in the medium category. Based on the result of the research, it can be concluded that the use of demontration methods can improve students ability in reading poetry students of class V SD Negeri 005 Koto Perambahan.